A Generalized Linear Model of a Navigation Network - Vinepinsky, Ehud; Perchik, Shay; Segev, Ronen (Frontiers in Neural Circuits, 2020)
Navigation by mammals is believed to rely on a network of neurons in the hippocampal formation, which includes the hippocampus, the medial entorhinal cortex (MEC) and additional nearby regions. Neurons in these regions represent spatial information by tuning to the position, orientation and speed of the animal in the form of head direction cells, speed cells, grid cells, border cells, and unclassified spatially modulated cells. While the properties of single cells are well studied, little is known about the functional structure of the network in the MEC. Here, we use a generalized linear model to study the network of spatially modulated cells in the MEC. We found connectivity patterns between all spatially encoding cells, and not only grid cells. In addition, the neurons’ past activity contributed to the overall activity patterns. Finally, position modulated cells and head direction cells differed in the dependence of the activity on the history. Our results indicate that MEC neurons form a local interacting network to support spatial information representations and suggest an explanation for their complex temporal properties.